A cadherin‐like protein influences Bacillus thuringiensis Cry1Ab toxicity in the oriental armyworm, Mythimna separata. Issue 3 (17th February 2013) - Wang, Ling; Jiang, Xingfu; Luo, Lizhi; Stanley, David; Sappington, Thomas W.; Zhang, Lei
Summary Cadherins comprise a family of calcium‐dependent cell adhesion proteins that act in cell–cell interactions. Cadherin‐like proteins (CADs) in midguts of some insects act as receptors that bind some of the toxins produced by the Bacillus thuringiensis (Bt). We cloned a CAD gene associated with larval midguts prepared from Mythimna separata. The full‐length cDNA (MsCAD1, GenBank Accession No. JF951432) is 5642 bp, with an open reading frame encoding a 1757 amino acid and characteristics typical of insect CADs. Expression of MsCAD1 is predominantly in midgut tissue, with highest expression in the 3rd‐ to 6th‐instars and lowest in newly hatched larvae. Knocking‐down MsCAD1 decreased Cry1Ab susceptibility, indicated by reduced developmental time, increased larval weight and reduced larval mortality. We expressed MsCAD1 in E. coli and recovered the recombinant protein, rMsCAD1, which binds Cry1Ab toxin. Truncation analysis and binding experiments revealed that a contiguous 209‐aa, located in CR11 and CR12, is the minimal Cry1Ab binding region. These results demonstrate that MsCAD1 is associated with Cry1Ab toxicity and is one of the Cry1Ab receptors in this insect. The significance of this work lies in identifying MsCAD1 as a Cry1Ab receptor, which helps understand the mechanism of Cry1Ab toxicity and of potential resistance to Bt in M. separata.